Characterisation of nanometric chromium coatings in metal-polymer composites. (1st September 2013) - Zumelzu, E; Angulo, C; Cabezas, C; Ugarte, R
<x xml:space="preserve">Abstract</x> Electrolytic chromium-coated steel (ECCS) plates are surface protected by a semi-crystalline polyethylene terephthalate (PET) polymer coating that provides mechanical and corrosion resistance properties. At the interface level, the steel is protected by a nanometric electrolytic chromium-based coating that chemically binds with the PET layer. However, axial deformations of the composite alter the chromium oxide layers, due to manufacturing surface discontinuities and the existence of detachment areas, producing adhesion failures, as well as changes in the surface and interfacial morphology of the composite, which limit its functionality. This study evaluated the correlations between delamination areas and uniaxial deformations, and assessed the effect on the chromium layers concerning protection and adherence. The results produced delamination maps, which showed the formation of microcracks on the chromium coatings, and indicated the changes that weakened the metal-polymer chemical bonds that consequently decrease the potential performance of industrial applications such as food containers.